Economic-financial and patrimonial elder abuse: a documentary study - Ana Maria Ribeiro dos Santos; Regina Dulce da Silva Nolêto; Rosalina Aparecida Partezani Rodrigues; Elaine Maria Leite Rangel Andrade; Elisiane Gomes Bonfim; Tatyanne Silva Rodrigues (SciELO, 2019)
ABSTRACT Objective: To analyze economic-financial and patrimonial cases of elder abuse, recorded in the specialized police station for security and protection of the elderly of a capital city in the northeast region of Brazil. Method: A cross-sectional study was carried out with data extracted from police reports and inquiries recorded in the abovementioned police station. Descriptive and inferential statistics were carried out by means of Pearson's chi-square test or Fisher's exact test, and multivariate logistic regression. Results: The sample was made up of 555 police reports. The data showed that financial abuse presented a prevalence of 58.9%, and that older elderly people (67.9%), men (70.4%), and single (75.0%) presented a higher percentage of financial abuse compared with other types of violence, often occurring in public places, with 3.1 more chances of occurrence than at the elderly's home. Regarding aggressors, women (73.5%), without suspicion of alcohol use (66.4%), and non-family members committed more financial abuse, evidencing 2.97 more chances of practicing it. Conclusion: In the period studied, financial abuse increased in its magnitude when compared with other types of violence, a fact that justifies researching the theme in order to prevent it.